Periodontal Microsurgery: Systematic Review and Meta-analysis - Veena Kalburgi; Shravani Bhole (Journal of Head & Neck Physicians and Surgeons)
Conventional surgeries involve larger areas including more soft- and hard-tissue manipulation which results in greater postoperative edema, inflammation, and pain. Microsurgery is an advanced surgical technique in which normal vision is enhanced through magnification of ×10 or more performed under a surgical microscope. Application of microsurgical principles is to achieve passive and primary wound closure. This systematic review was carried out in accordance with the Cochrane Handbook for Systematic Reviews of Interventions and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. Microsurgery was observed to be better following different periodontal surgeries when compared to the parameters of recession depth, recession width, and clinical attachment level. However, inconclusive evidence was seen for the variables of probing depth and width of keratinized tissue. The study found that the microsurgical approach resulted in less postoperative pain and discomfort compared to the macrosurgical method. The microsurgical instrument tools contributed to improved wound stabilization and better flap adaptation. When deciding between macrosurgical and microsurgical procedures, it is important to consider factors such as treatment outcomes, logistics, cost, and patient-centered parameters.